2011
DOI: 10.1007/7854_2011_186
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Genetics of the Serotonin Transporter

Abstract: The serotonin transporter is a key regulator of the bioavailability of serotonin and therefore any modulation in the expression or action of the transporter would be expected to have consequences on behaviour. The transporter has therefore become a target for pharmaceutical intervention in behavioural and mood disorders. The search for polymorphic variants in the transporter that would associate with neurological disorders has been extensive but has become focused on two domains which are both termed variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 203 publications
0
23
1
1
Order By: Relevance
“…Superimposed on these regulatory parameters could be modulation of their activity by the polymorphic nature of the distinct domains within the SVA such as the VNTR elements. There is an extensive literature on VNTR domains both being differentially associated with disease and transcriptional properties based on the copy number of the repeats [29,50]. In this study we addressed firstly the site of integration of SVA elements, secondly the potential secondary structures formed and finally a detailed analysis of the PARK7 SVA’s ability to support reporter gene expression and its polymorphic nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superimposed on these regulatory parameters could be modulation of their activity by the polymorphic nature of the distinct domains within the SVA such as the VNTR elements. There is an extensive literature on VNTR domains both being differentially associated with disease and transcriptional properties based on the copy number of the repeats [29,50]. In this study we addressed firstly the site of integration of SVA elements, secondly the potential secondary structures formed and finally a detailed analysis of the PARK7 SVA’s ability to support reporter gene expression and its polymorphic nature.…”
Section: Discussionmentioning
confidence: 99%
“…This differential regulator property has been correlated with copy number of the VNTR in some genes [30,34-43]. For example, we and others have demonstrated that VNTRs located in the promoter and second intron of the human serotonin transporter gene ( SLC6A4 ) are differential as both risk factors for mental health and tissue specific regulators in the context of reporter gene constructs, in vivo and in vitro based on the copy number of the repeat [29,31,35]. …”
Section: Introductionmentioning
confidence: 99%
“…The promoter region of this gene has either 14 (short) or 16 (long) copies of a 22 base pair repeat polymorphism ( 5-HTTLPR ) located 1200 nucleotides upstream of the transcriptional start site (Lesch et al, 1996; Haddley et al, 2012). The classic long “L” and short “S” alleles (rs4795541) (Lesch et al, 1996) were determined by PCR amplification of DNA to yield a 181 base pair (bp) fragment for the L allele and a 138 bp fragment for the S allele (Hu et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Apart from being expressed in 5-HT neurons, the 5-HTT is also transiently expressed in non-aminergic neurons, belonging to many topographically distinct brain areas (Lebrand et al, 1998; Zhou et al, 2000; Narboux-Neme et al, 2008; Kalueff et al, 2010). In humans, the 5-HTT gene-linked polymorphic region (5-HTTLPR), composed of a short and a long version (Canli and Lesch, 2007; Neumann et al, 2011; Haddley et al, 2012), affects 5-HTT expression and function. The short (s) variant has been associated with robust neurodevelopmental changes in corticolimbic structures, and increased risk for depression in the context of stress (Canli and Lesch, 2007).…”
Section: Introductionmentioning
confidence: 99%